Aortic arch surgery for type B aortic dissection: How far should we go? The value of a hybrid approach. Issue 1 (3rd January 2023) - Capoccia, Massimo; Sherif, Mohamed Ashur; Nassef, Ahmed; Shaw, David; Walker, Paul; Evans, Betsy; Kaul, Pankaj; Elmahdy, Walid
Abstract: Traditionally, the management of type B aortic dissection has been the domain of the vascular surgeons. Timing and type of intervention still generate debate. We sought to review our early experience with the treatment of this condition based on a hybrid approach following an aortic multi‐disciplinary team meeting involving close cooperation between cardiac surgeons, vascular surgeons, interventional radiologists, vascular anesthetists, and cardiac anesthetists. Four patients (age 41–56 years; 3 males; 1 female) with type B aortic dissection underwent aortic arch surgery through a hybrid approach: one elective procedure consisting of ascending aorta and hemi‐arch replacement with debranching followed by thoracic endovascular aortic repair (TEVAR); one redo procedure requiring aortic arch replacement with hybrid frozen elephant trunk; two acute presentations (aortic arch replacement and debranching followed by TEVAR; AVR with ascending aorta, arch, and proximal descending thoracic aorta replacement with conventional elephant trunk and debranching). Deep hypothermic circulatory arrest was required in three patients. Despite respiratory complications and slightly prolonged postoperative course, all patients survived without onset of stroke, paraplegia, malperfusion, endoleak, or need for re‐exploration. Follow‐up remains satisfactory. Different factors may affect outcome following complex aortic procedures. Nevertheless, close cooperation between cardiac surgeons, vascular surgeons, and interventional radiologists may reduce potential for complications and address aspects that may not be completely within the domain of individual specialists. Abstract : Surgical treatment for aortic disease remains challenging and demanding. Treatment often needs to be tailored to the patient or the group of patients being referred. A hybrid approach may have a role to play as an additional option to the surgical armamentarium. Cooperation between different specialists is essential.